Electronically Tunable Capacitance Multiplier Implemented Using a Single Active Element for Low-Frequency Biomedical Applications - Chaichana, Amornchai; Suwanjan, Peerawut; Siripongdee, Surapong; Jaikla, Winai (My University, 2024)
An active circuit designed for increasing a passive capacitor's capacitance to a noticeably larger level is called a capacitance multiplier. The article proposes the design of a grounded capacitance multiplier using an electronically adjustable active device called a voltage differencing differential difference amplifier (VDDDA). The proposed capacitance multiplier is a very compact structure that consists of just one passive resistor, one passive capacitor, and one VDDDA. The multiplication factor (KC) can be electronically controlled by adjusting the external bias current (IB) of VDDDA, which is convenient for microcontroller control in modern analog signal processing systems. To test the performance of the proposed capacitance multipliers PSpice simulation and experimentation using a VDDDA built from commercially available integrated circuits were utilized. To further illustrate the usefulness of the proposed capacitance multiplier, an application example in the lagged phase shifter with electronically adjustable phase shifts is shown and examined.
Keywords: capacitance multiplier; electronic control; phase shifter; VDDDA